Revisiting the Öndör Ulaan Site (Studia Archaeologica, 2025)
The issue of the continuity of Xiongnu burial traditions, which were widely distributed across vast territories, has long been a subject of scholarly interest. Therefore, in the study of the burial customs of the Xianbei, Rouran, and later Mongols, the earthen mound located at the foot of Öndör Ulaan Mountain and the tomb discovered there have provided important materials. Based on the excavation process, the artifacts unearthed from the tomb, and the laboratory results of radiocarbon dating of the human remains, this study attempts to reaffirm and further interpret the findings of previous research. The earthen mound at Öndör Ulaan is considered to have been constructed during the period of the Xiongnu Empire, in comparison with the “Three Fortresses of the Steppe.” However, after being abandoned for some reason, a secondary intrusive burial was later placed on top of it. The earlier research that dated the tomb to the late 4th–early 5th century CE has been confirmed by laboratory analysis (381–425 CE), indicating that it belongs to the period of the Rouran Khaganate. Historical accounts mention that during the political conflicts between the Xiongnu and Han empires, the desecration and looting of ancestral tombs caused deep moral and cultural trauma. As a result, burial practices shifted toward concealing graves without surface markers, interment in caves or rock shelters, and cremation—a tradition that was subsequently inherited by nomadic tribes across the steppe. The Öndör Ulaan tomb, as one of the few archaeological remains representing the Rouran period, provides valuable material for studying the funerary culture of post-Xiongnu nomads.Өндөр улааны дурсгалын тухай дахин өгүүлэх ньХураангуй. Харьцангуй өргөн хүрээнд тархсан хүннүгийн булш оршуулгын залгамж холбооны асуудал ямагт анхаарал татсаар байгаа сэдэв юм. Иймээс Сяньби, Жужаны булш оршуулга хийгээд хожмын монголчуудын оршуулгын дурсгалын судалгаанд Өндөр улаан уулын өвөрт буй шороон дов, тэндээс илэрсэн булш чухал материал болсон юм. Уг дурсгалын малтлагын явц, булшнаас илэрсэн эд өлгийн зүйл хийгээд нас барагчийн яснаас авсан дээжийн он цаг тогтоох лабораторийн хариунд тулгуурлан өмнөх судалгааны үр дүнг бататган, тайлбарлах оролдлого хийлээ. Өндөр улааны шороон довыг Талын гурван хэрэмтэй харьцуулан Хүннү улсын үед бүтээгдсэн хэмээн үзэж байна. Харин ямар нэгэн шалтгаанаас дутуу орхиж хулширсны дараа оруулмал булшийг дээр нь үйлджээ. Булшийг IV зууны төгсгөлөөс V зууны эхэнд холбогдуулсан өмнөх судалгааг лабораторийн дээжийн хариуд (НТ381-425 он) тулгуурлан Жужан улсын үед холбогдохыг бататган тогтоолоо. Хүннү, Хангийн улс төрийн тэмцэлд өвөг дээдсийн онгон хүүрийг тонож доромжлох явдал гарсан нь асар их сургамж болсон тул оршуулгын хөрсний дээр ямар нэгэн тэмдэг тавилгүй нуух, агуй хад чулууны хөмөгт дарах, чандарлах зан үйл давамгайлж улмаар тал нутгийн овог аймгуудад уламжлагдсан гэсэн судлаачдын саналыг бататгах нэгэн баримт болно. Өндөр улааны дурсгалаас олдсон булш нь жужаны үеийг төлөөлөх цөөн дурсгалын нэг болсноор цаашид хүннүгийн дараах нүүдэлчдийн оршуулгын соёлыг судлахад үнэтэй хэрэглэгдэхүүн болох нь дамжиггүй.Түлхүүр үг: Шороон дов, Өндөр улааны булш, он цаг, Жужан